PENGEMBANGAN MEDIA ECO VENTURE PADA PEMBELAJARAN IPAS MATERI EKOSISTEM TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS V SEKOLAH DASAR - Kunaifi, Aang; Lutfi Choirunnisa, Nadia; Julianto; Istianah, Farida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teaching natural and social sciences on the topic of ecosystems in elementary school requires instructional media capable of presenting concepts in a concrete and interactive manner. Preliminary research conducted at SDN Sukomanunggal I/105 showed that the learning process is still dominated by the use of simple media, such as pictures, resulting in low student engagement and learning outcomes that have not yet met the Learning Mastery Criteria. This study aims to develop Eco Venture as a learning medium that integrates a board game, augmented reality (AR)-based flashcards and WordWall, as well as a flipbook as a user guide to improve students’ learning outcomes on the ecosystem unit for fifth-grade elementary school students. The study employed the Research and Development (R&D) method using the ADDIE development model, which includes the Analyze, Design, Development, Implementation, and Evaluation stages. Data collection was conducted using expert validation sheets, practicality questionnaires, pretest, and posttest. The data were then analyzed using percentage analysis, normality tests, paired-samples t-tests, N-Gain tests, and effect size tests. The results of the study show that the Eco Venture medium achieved a validity level of 93.75%, categorized as “highly valid”; a practicality level of 94.50%, categorized as “highly practical”; and an N-Gain value of 0.72, categorized as “high.” Consequently, it was deemed effective in improving the learning outcomes of elementary school students. Overall, the Eco Venture media is suitable for use as an innovative learning medium in elementary school Natural and Social Sciences classes covering the topic of ecosystems, as it meets the criteria for validity, practicality, and effectiveness.